Death and the maiden : the curious relationship between the fear of the feminine and the fear of death - Burke, Brigid, 1972- (Algora Publishing, 2019)
"Belief in an immortal soul and in salvation has a paradoxically negative impact on perceptions of the archetypal feminine in myth, religious scripture, and philosophy; this can be demonstrated using the lens of depth psychology. This book explores the idea from Ancient Egyptian times through the early Christian era"--